First record of species pseudodactylogyrus anguillae (Yin &Sproston, 1948) on the gills of eels fish ( Angilla Anguilla L.) in SYRIA - Dayoub, Amal Ibrahim (Latakia University Journal -Biological Sciences Series, 2013)
Study was performed in aiming to detect the occurrence of pseudodactylogyrus spp. worms on gills of eels Fish ( Anguilla Anguilla L) in Al kabeer Al shamali River. Fish samples were collectedfrom different places of Al kabeer Al shamali river, randomlytwice a season , during the period from 28/1/2013 until 15/8/2013. Eels fish were minimally distributed 5.17% inAl kabeer Al shamali River. The study has shown presence of one species ofpseudodactylogyruson the gills of eels fish is: pseudodactylogyrusanguillae, This speices is classified for the first time in Syria in this study.